Objectlogic - Tan, Siew Hua (2019)
Objectlogic is an interactive installation that uses everyday objects to create whimsical sentences that are logical yet nonsensical at the same time. It is made up of two segments where the first is an station that holds an archive collection of sentences formed by others and myself based on the mixture of objects I curated in each box. The second is an AI program that will try to make sense of objects given by visitors while helping them to creating a whimsical sentence of their own. The interactive space allows visitors to be momentarily distracted from their troubles or hectic lives while questioning our need for reliance on technology for everything now, even to the extent for something “nonsensical”?